2002
DOI: 10.1097/00003246-200201000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin is associated with endotoxin tolerance in mice

Abstract: These results demonstrate that mice with an increased concentration of thioredoxin, induced by pretreatment with a low dose of lipopolysaccharide, had increased survival when given a subsequent high-dose challenge of lipopolysaccharide. Thus, thioredoxin is associated with the development of endotoxin tolerance in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…The first study showed that the induction of glutamate cysteine ligase may be an important adaptive response of the alveolar epithelium when under attack by oxidative stress and by lipid peroxidation products such as 4-hydroxy-2-nonenal [91]. A second study has shown that another antioxidant, the thioredoxin gene, is induced by 4-hydroxy-2-nonenal in response to LPS challenge in mice, thereby providing endotoxin tolerance [92].…”
Section: S-glutathiolation Modulation Of Transcription Factorsmentioning
confidence: 99%
“…The first study showed that the induction of glutamate cysteine ligase may be an important adaptive response of the alveolar epithelium when under attack by oxidative stress and by lipid peroxidation products such as 4-hydroxy-2-nonenal [91]. A second study has shown that another antioxidant, the thioredoxin gene, is induced by 4-hydroxy-2-nonenal in response to LPS challenge in mice, thereby providing endotoxin tolerance [92].…”
Section: S-glutathiolation Modulation Of Transcription Factorsmentioning
confidence: 99%
“…The second Grx (Grx2) gene, which was reported recently, encodes two proteins as a result of alteration of RNA splicing. One of the Grx2 isoforms is located in the mitochondria and the other in the nucleus (54,55). Similar to Trx, Grx also functions in catalyzing thiol/disulfide exchange (57).…”
Section: Dasmentioning
confidence: 99%
“…For example, oxidative stress can easily induce the expression of Trx1 (17,51). A recent study showed that pretreatment of mice with a sublethal dose of lipopolysaccharides increased Trx concentrations that played an important role in the development of endotoxin tolerance via inhibition of ROS (55).…”
Section: Introductionmentioning
confidence: 99%
“…TSA and thioredoxin, two main antioxidant proteins, are likely to be important not only in general cell protection, but also in the promotion of infection and invasion by these pathogenic organisms through protecting against oxidative attack by activated host phagocytic cells [33][34][35]. Following a burn, there is an enormous production of reactive oxygen species (ROS), which is harmful and implicated in inflammation, infection, sepsis, tissue damage, and multiple organ failure [36].…”
Section: Discussionmentioning
confidence: 99%